Yaoi Manga and Fujoshis: Exploration of the Own Voice of Desire as an Alternative to the Governance of Youth Sexuality - Chocontá Piraquive, Alexandra; Investigadora Independiente, Bogotá, Colombia (Editorial Pontificia Universidad Javeriana, 2014)
This article introduces a reflection on the adoption in Colombia of yaoi manga –Japanese comics that narrate homoerotic stories among men– by young fan girls known as fujoshis. It is suggested that in this space of consumption the fans develop their own voice of feminine desire, as an alternative to the governance of sexuality in youths. Said governance imposes specific ways of self-restrain and self-control of female sexuality in youths, based on an ideal type the way to be a woman. This own voice of desire is reconstructed in the article through the contextualization of yaoi manga and its arrival to the country, how fans have access to it, and how they get to interpret it.